2023
DOI: 10.1186/s13007-023-01003-3
|View full text |Cite
|
Sign up to set email alerts
|

Peat-based hairy root transformation using Rhizobium rhizogenes as a rapid and efficient tool for easily exploring potential genes related to root-knot nematode parasitism and host response

Abstract: Background Root-knot nematodes (RKNs) pose a worldwide threat to agriculture of many crops including cucumber. Genetic transformation (GT) has emerged as a powerful tool for exploration of plant-RKN interactions and genetic improvement of RKN resistance. However, it is usually difficult to achieve a highly efficient and stable GT protocol for most crops due to the complexity of this process. Results Here we firstly applied the hairy root transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The use of in vitro roots transformed with R. rhizogenes is not new and was previously studied in combination with RKNs to uncover important mechanisms of plant-nematode interactions, e.g., in analyzing the biochemical mechanisms of RKN parasitism [38], for characterizing and/or validating candidate genes for host resistance to RKNs [39][40][41][42], in propagating RKN resistant plant genotypes [43], in understanding the processes of RKN infection after knocking out specific stress-related or putative susceptibility genes [44], or for the general maintenance of RKN collections [45][46][47]. However, resorting to plantnematode co-cultures as a tool to uncover bioactive compounds or mixtures for the design of safer biopesticides is less reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The use of in vitro roots transformed with R. rhizogenes is not new and was previously studied in combination with RKNs to uncover important mechanisms of plant-nematode interactions, e.g., in analyzing the biochemical mechanisms of RKN parasitism [38], for characterizing and/or validating candidate genes for host resistance to RKNs [39][40][41][42], in propagating RKN resistant plant genotypes [43], in understanding the processes of RKN infection after knocking out specific stress-related or putative susceptibility genes [44], or for the general maintenance of RKN collections [45][46][47]. However, resorting to plantnematode co-cultures as a tool to uncover bioactive compounds or mixtures for the design of safer biopesticides is less reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that cotyledon as explants produce more hairy roots than hypocotyl segments in cotton and other plants [ 37 ]. For example, cotyledon node injection allows faster and more efficient in vivo studies of root development in cucumber than hypocotyl cutting injection [ 38 ]. However, in some cases, hypocotyls can yield a higher transformation efficiency that depends on plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Cucumber hairy root transformation was performed using R. rhizogenes K599 as detailed in Zhang et al ( 2023 ). A promoter region of about 2000 bp of CsPTS (CsaV3_3G028840) and CsCHS (CsaV3_3G027830) was amplified and cloned into the pCAMBIA 1391‐GUS vector.…”
Section: Methodsmentioning
confidence: 99%